Effects of Strain and Species on the Septo-Temporal Distribution of Adult Neurogenesis in Rodents - Wiget, Franziska; van Dijk, R. Maarten; Louet, Estelle R.; Slomianka, Lutz; Amrein, Irmgard (Frontiers in Neuroscience, 2017)
The functional septo-temporal (dorso-ventral) differentiation of the hippocampus is accompanied by gradients of adult hippocampal neurogenesis (AHN) in laboratory rodents. An extensive septal AHN in laboratory mice suggests an emphasis on a relation of AHN to tasks that also depend on the septal hippocampus. Domestication experiments indicate that AHN dynamics along the longitudinal axis are subject to selective pressure, questioning if the septal emphasis of AHN in laboratory mice is a rule applying to rodents in general. In this study, we used C57BL/6 and DBA2/Crl mice, wild-derived F1 house mice and wild-captured wood mice and bank voles to look for evidence of strain and species specific septo-temporal differences in AHN. We confirmed the septal > temporal gradient in C57BL/6 mice, but in the wild species, AHN was low septally and high temporally. Emphasis on the temporal hippocampus was particularly strong for doublecortin positive (DCX+) young neurons and more pronounced in bank voles than in wood mice. The temporal shift was stronger in female wood mice than in males, while we did not see sex differences in bank voles. AHN was overall low in DBA and F1 house mice, but they exhibited the same inversed gradient as wood mice and bank voles. DCX+ young neurons were usually confined to the subgranular zone and deep granule cell layer. This pattern was seen in all animals in the septal and intermediate dentate gyrus. In bank voles and wood mice however, the majority of temporal DCX+ cells were radially dispersed throughout the granule cell layer. Some but not all of the septo-temporal differences were accompanied by changes in the DCX+/Ki67+ cell ratios, suggesting that new neuron numbers can be regulated by both proliferation or the time course of maturation and survival of young neurons. Some of the septo-temporal differences we observe have also been found in laboratory rodents after the experimental manipulation of the molecular mechanisms that control AHN. Adaptations of AHN under natural conditions may operate on these or similar mechanisms, adjusting neurogenesis to the requirements of hippocampal function.